Agama dan Kearifan Lokal Dalam Pengembangan Integrasi Sosial - Mufida, Aini; Hidayat, Mansur (BINA' AL-UMMAH, 2019)
This study describes a reality of relations and interactions between two groups of people based on religious and cultural differences. Awareness of the existing differences that could trigger conflict between the two groups, encourage the creation of local wisdom to adapting to culture and even adaptability to the pattern of applicating respective religious teachings, so that the harmonious relations between the two different groups, could be established and became a supporting factor for establishing social, cultural and economic dynamics of both parties. This research was conducted using a qualitative approach, specially  phenomenological approach. The results of the study explained that cultural ability in adapting and selecting of patterns in impelementing cultural values and teaching and selecting the appropriate pattern of religious teachings, became a determinant factor in preventing conflict and maintaining harmony in the relation and iteraction between two group of different communities.